PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA KELAS VI SD TULUNG MELALUI MODEL PEMBELAJARAN SNOWBALL THROWING - Wahyem Wahyem (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2018)
This study purposes to improve result of learning social sciences about Indonesians role in the era of globalization by the 6 grade of Tulung Elementary School. The actions study of the class is designed by model learning snowball throwing, which are process of planning, action, observations,and reflection. The techniques of collecting data do with the observations and test. The results of research by using model of learning snowball throwing has improved the result of the student learning. On the first cycle of learn reach 42,87%, that was not finished 52.17%. In the second cycle, 86,95% has completed and just 13,04% of the student that was not completed. The completeness achievement shows that it has been fulfilled complete criteria of at least targeted the 85% with the value of >75. The suggests that a model of learning snowball throwing have been able to improve results learn students of class 6 Tulung Elementary school